2021
DOI: 10.1093/ckj/sfab056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic kidney diseases as an underrecognized cause of chronic kidney disease: the key role of international registry reports

Abstract: Inherited kidney diseases (IKDs) are among the leading causes of early-onset chronic kidney disease (CKD) and are responsible for at least 10–15% of cases of kidney replacement therapy (KRT) in adults. Pediatric nephrologists are very aware of the high prevalence of IKDs among their patients, but this is not the case for adult nephrologists. Recent publications have demonstrated that monogenic diseases account for a significant percentage of adult cases of CKD. A substantial number of these patients have recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 51 publications
0
48
0
Order By: Relevance
“…Published studies suggested the same pattern [24]. Inherited kidney diseases (IKDs) are considered as the foremost reasons for the initiation of CKD and are accounted for about 10-15% of kidney replacement therapies (KRT) in adults [30].…”
Section: Discussionmentioning
confidence: 91%
“…Published studies suggested the same pattern [24]. Inherited kidney diseases (IKDs) are considered as the foremost reasons for the initiation of CKD and are accounted for about 10-15% of kidney replacement therapies (KRT) in adults [30].…”
Section: Discussionmentioning
confidence: 91%
“…Genomic medicine is increasingly promoting personalized approaches to define diagnostic trajectories of inherited kidney diseases [ 30 , 32 ]. In patients with salt-losing tubulopathies, precision medicine claims to build up strategies to cover diagnostic and phenotypic areas of uncertainty in order to inform treatment, prognosis and counseling.…”
Section: Discussionmentioning
confidence: 99%
“…18 , 19 , 21 While PKD is the only inherited kidney disease usually reported by large registries, recent Madrid and Catalonian KRT registry data found all inherited kidney diseases combined as frequent as glomerulonephritis. 22 Inherited kidney diseases are frequently overlooked by physicians. Indeed, whole exome sequencing found monogenic kidney diseases in 9% of adult CKD, and in 17–34% of those with CKD of unknown cause.…”
Section: The Most Common Cause Of Ckd Is Unknown: the Need To Redefine The Ckd Etiology Landscapementioning
confidence: 99%